Communicating clocks shape circadian homeostasis - Koronowski, Kevin B.; Sassone-Corsi, Paolo (Science (American Association for the Advancement of Science), 2021)
Circadian rhythms that affect multiple tissues and organ systems are aligned with the dark-light cycle and other external inputs such as feeding. But how is such time keeping modulated throughout complex systems and anatomical regions? Koronowski and Sassone-Corsi reviewed how central regulators in the brain and peripheral regulators throughout organs can behave cooperatively or independently to modulate circadian rhythms. This systemic view of circadian rhythm modulation is important to understand behavior and disease, because dysregulated clocks are associated with metabolic syndrome and cancer. Science , this issue p. eabd0951 Circadian clocks temporally coordinate physiology and align it with geophysical time, which enables diverse life-forms to anticipate daily environmental cycles. In complex organisms, clock function originates from the molecular oscillator within each cell and builds upward anatomically into an organism-wide system. Recent advances have transformed our understanding of how clocks are connected to achieve coherence across tissues. Circadian misalignment, often imposed in modern society, disrupts coordination among clocks and has been linked to diseases ranging from metabolic syndrome to cancer. Thus, uncovering the physiological circuits whereby biological clocks achieve coherence will inform on both challenges and opportunities in human health.